PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN LOYALITAS BAGIAN KANTOR PADA PT. RAMAJAYA PRAMUKTI KABUPATEN KAMPAR - Diky Mahyudi; Nuryanti '; Haryetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the influence of organizational culture and work motivation on job satisfaction and loyalty of employees at PT. Ramajaya Pramukti Kabupaten Kampar. The population in this study were all employees of the office at PT. Ramajaya Pramukti Kabupaten Kampar totaling 102 people. While the sampling technique using census method. Analysis of data using multiple linear regression with SPSS version 18.00. Based on the results of data analysis known that the organizational culture affect the job satisfaction of employees, work motivation influence on job satisfaction of employees, organizational culture influence on employee loyalty r, motivation effect on employee loyalty, job satisfaction effect on employee, organizational culture influence on employee loyalty through employee satisfaction, and work motivation influence on employee loyalty through employee satisfaction in. To maximize the loyalty of employees, should Personality sense of having employees of the company are very high, to maximize job satisfaction of employees, companies should give a salary appropriate and balanced with the workload on the responsibility of employees, to maximize organizational culture, is expected Employees always take into account the risks to all problems that may occur, to maximize employee motivation, then it should be safety of employees at work is always guaranteed.Keywords: Culture, Motivation, Satisfaction and Loyalty